Epileptics and burns - Bukovčan, P; Koller, J (Acta chirurgiae plasticae, 2013)
BACKGROUND: The aim of this paper is to ascertain the number of patients with a burn injury sustained during an epileptic seizure treated in our facility, to identify the characteristics of these types of injuries and to suggest preventive measures, which could reduce the frequency and morbidity of such injuries. PATIENTS AND METHODS: We performed a retrospective study, identifying all patients admitted with burns sustained during an epileptic seizure within a period of six years. RESULTS: Totally 7 women with an average age of 45 years were enrolled in this retrospective study. Mean BSAB was 2.4% (range 0.5-6). All burns occurred in a domestic setting during household activities (cooking, ironing). Thermal injury included contact burn (6 patients with deep burns), followed by scald (one patient with superficial burns). 6 of 7 patients (85%) required excision of deep burns and skin grafting procedure. The average duration of hospital stay was 13 days. Collected data were compared with the results and findings of similar studies and analysed. A list of preventive measures is included. CONCLUSION: Patients with epilepsy should be informed about all potential threats at the time of neurological diagnosis including also the risk of serious burn injury, which should be emphasised.
Keywords: dospělí; povrch těla; Epilepsy; Female; popáleninové jednotky; Adult; ženské pohlaví; Registries; Body Surface Area; Slovakia; lidé; retrospektivní studie; epilepsie; Burns; Burn Units; lidé středního věku; registrace; Slovenská republika; popálení; Retrospective Studies; Middle Aged; Humans